De novo Portal Vein Thrombosis in Non-Cirrhotic Non-Alcoholic Fatty Liver Disease: A 9-Year Prospective Cohort Study - Abdel-Razik, Ahmed; Mousa, Nasser; Shabana, Walaa; Yassen, Ahmed H.; Abdelsalam, Mostafa; Wahba, Mohamed M.; Helmy, Eman Mohamed; Tawfik, Ahmed M.; Zalata, Khaled; Hasan, Ahmad S.; Elhelaly, Rania; Elzehery, Rasha; et al. (Frontiers in Medicine, 2021)
Background & Aims Approximately 30–40% of portal vein thrombosis (PVT) remains of unknown origin. The association between nonalcoholic fatty liver diseases (NAFLD) and PVT is a matter of debate. The aim of this study was to investigate the association between PVT and NAFLD. Methods Ninety-four out of 105 consecutive NAFLD patients were included in this prospective cohort study in addition to 94 healthy control group. Biochemical, clinical, immunological, histopathological parameters, waist circumference (WC), leptin, adiponectin, and leptin/adiponectin ratio (LAR) were evaluated for all participants at baseline and every 3 years thereafter. The characteristics of participants at baseline were described. Individual WC, LAR, and characteristics of PVT are also shown. Potential parameters to predict PVT development within 9 years were determined. Results PVT developed in 8 (8.5%) patients, mainly in the portal trunk. Univariate analysis showed three PVT-associated factors; diabetes mellitus (P=0.013), waist circumference (P<0.001), and LAR (P=0.002). After adjusting multiple confounding variables, the multivariate model showed that waist circumference and LAR were only significant. By applying the receiver operating characteristic curve, at cutoff values of >105 cm, waist circumference had 98.8% specificity, 87.5% sensitivity, 0.894 area under the curve (AUC) for prediction of PVT (P<0.001). As well, at cutoff values of >7.5, LAR had 60.5% specificity, 87.5% sensitivity, 0.805 AUC for PVT prediction (P<0.001). Conclusions This study suggests that increased central obesity and LAR were independently associated with PVT development in non-cirrhotic NAFLD patients, and they should be considered as risk factors that may participate in PVT multifactorial pathogenesis.